Lightweight biopolymer drilling fluid for underbalanced drilling: An optimization study - Nee, L.S.; Khalil, M.; Jan, B.M.; Ali, B.S. (Elsevier, 2015)
This paper presents an optimization of a lightweight biopolymer drilling fluid for underbalanced drilling (UBD) using Response Surface Methodology (RSM). Concentrations of four raw materials (glass bubbles, clay, xanthan gum and starch) were varied to analyze their effects on three vital responses: density, plastic viscosity (PV) and yield point (YE') of the fluid. Based on the results, the optimum condition was achieved at concentrations of glass bubbles, clay, xanthan gum and starch of 24.46 w/v,0.63 w/v, 0.21 w/v and 2.41 w/v, respectively. The results showed that it is possible to predict the three response parameters using models generated by RSM since the experimental values were found to be in good agreement with the predicted values (error <1.0, standard deviation < 0.5 and accuracy > 98.5). (C) 2015 Elsevier B.V. All rights reserved.